Past distribution (21,000 yrs) of the ground beetle Pelmatellus columbianus in Ecuador - Munoz-Tobar, Sofia Isabel (Clemson University, South Carolina, 2018)
This dataset contains raster grids in TIFF format describing the past distribution (21000 yrs) of Pelmatellus columbianus in continental Ecuador. The spatial resolution is 2.5 m x 2.5 m.